THE INFLUENCE OF TYPE MODIFICATOR ON ADHESIVE BEHAVIOR OF POLYMERIC COMPOSITIONS FOR REPAIR BUILDINGS’ DECORATIVE ELEMENTS - A. P. Prihodko; E. S. Harchenko (Nauka ta progres transportu, 2010)
In the article the basic research results of influence of modifier type and amount on adhesive properties of polymeric compositions for repairing the structure decorative elements are presented. The modifier is described and the adhesion strength indices for the modified polymeric solution and the repaired surface are determined.